Bidirectional Power Performance of a Tidal Unit with Unilateral and Double Guide Vanes. (8th October 2013) - Yang, Chunxia; Zheng, Yuan; Zhou, Daqing; Ge, Xinfeng; Li, Lingyu
Abstract : To improve the bidirectional power performance of a tidal unit, two designs were investigated. The use of unilateral or double guide vanes in a tubular tidal unit influences the performance of the hydraulic unit. Based on the N-S equations and the RNG k -ε turbulence model, the SIMPLEC algorithm was used for 3D steady-state numerical simulation of the entire turbine flow passage with unilateral and double guide vanes. The internal flow condition under positive and reverse power generation conditions was also analyzed. At the same time, the turbine, with a runner 1.6 m in diameter, was scaled down to 0.35 m diameter for model tests. The model tests were based on a multifunction hydromechanical test bench at Hohai University. The water head, discharge, and torque of the tubular turbine were, respectively, tested using a pressure difference sensor, electromagnetic flow meter, and torque meter under different guide-vane openings. The results show that turbine efficiency in the model test is slightly lower than that predicted by numerical simulation under the same conditions. However, the difference is not large. With double side guide vanes, although the efficiency of positive power generation decreased, the efficiency of reverse power generation is greatly improved.